Listening to Funeral Directors in Rural Oklahoma Funeral Homes: Social Construction of Roles, Goals, and Strategies. Issue 4 (8th August 2021) - Bi, Da; Hammonds, Kyle A.
ABSTRACT: This study examined rural funeral directors' performance of social roles. Seventeen funeral directors were recruited from rural Oklahoma funeral homes for in-depth interviews. Constant comparative analysis was used to construct a typology of directors' roles, goals, and strategies. The typology focuses on the relation between roles and performances from the group communication perspective. The study found that rural funeral directors had four major self-perceived roles: professional, restorative artist, supporter, and educator. These roles reflect social functions of funeral homes in rural communities and how directors discursively operationalize those functions. These goals and strategies demonstrate role-making and role-taking processes in the funeral home context. Finally, the study discusses tensions in the social roles assumed by rural funeral directors for future research.